PANDEMIC CORONA: CHANGES IN BUREAUCRATIC APPLYING WORK FROM HOME - Herru Setiadhie; Hardi Warsono (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2020)
The spread of the Corona Virus or Covid-19 Virus is a global pandemic affecting all countries, including Indonesia. To erode the spread of the corona virus, efforts are being made to limit the crowd, always wash hands and live cleanly, as well as social distance. For this reason, all sectors of activity need to make changes. One fundamental change is the adoption of Work from Home (WFH) for bureaucratic apparatus. WFH is a concept of work change that was originally done in the office turned into a remote work pattern using IT applications. Through Lewin's model, change management in the application of WFH is observed. Through documentary studies and surveys, the change management can be elaborated to find out how WFH is applied, the constraints and responses of the apparatus in working in a pandemic.